The Effect of Creativity and Learning Independence on the Speaking Skill of Class V Students of Elementary Schools in Agus Salim Group, Buluspesantren - Siti Muslimah; Rokhmaniyah Rokhmaniyah; Muhammad Husni Arifin (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2022)
This research is based on the problem of students' speaking skills that have not been satisfactory. This study aims to determine the effect of creativity and independent learning on speaking skills in fifth-grade elementary school students in the Agus Salim Bulus Pesantren cluster. This research is quantitative. The sample of this research is several existing populations, namely 120 students. Collecting data using questionnaires and observations. Data analysis used simple linear regression and multiple linear regression. This study resulted in the following conclusions (1) Creativity has a positive effect on speaking skills in fifth-grade elementary school students in the Agus Salim Bulus Pesantren Cluster, as evidenced by the value of Sig = 0.000 < = 0.050. The value of the correlation coefficient (r2) = 0.206 or contributed 20.6%. (2) Learning independence has a positive effect on speaking skills in fifth-grade elementary school students in the Agus Salim Bulus Pesantren Cluster, as evidenced by the value of Sig = 0.005 < = 0.050. The value of the correlation coefficient (r2) = 0.065 or contributed 6.5%. (3) Creativity and independent learning together have a positive effect on speaking skills in fifth-grade elementary school students in Agus Salim Bulus Pesantren, as evidenced by the value of Sig = 0.000 < = 0.050. The value of the correlation coefficient (R2) = 0.219 or contributed 21.9%.